A Cross-Sectional Study on Menstrual Health Practice and Needs Among Female Rohingya Residing in Malaysia: An Interim Analysis - Badrul Hisham, Muhammad Aqif; Mohamed Tahir, Ahmad Rashidi; Syed Hussein Al-Attas, Sh Fatimah AlZahrah; Athirah Daud, Nur Aizati (International Journal of Human and Health Sciences (IJHHS), 2023)
Objectives: Not much is known about the menstrual practices and needs among Rohingya females residing in Malaysia. This knowledge gap needs to be addressed, in line with the efforts toward family planning. The objectives of the study are to describe menstrual practices among female Rohingya and to assess whether their menstrual needs are met during their last period. Methods: This is a cross-sectional study involving Rohingya females aged 18 to 55 years old attending QFFD Clinic run by IMARET in Selayang, Selangor between April to July 2022. Menstrual practices and needs were assessed using self-administered questionnaires; the Menstrual Practices Questionnaire (MPQ) and the Menstrual Practice Needs Scale (MPNS-36), respectively. Results: A total of 40 respondents have completed the questionnaire. Only 42.5% (n=17) of respondents have good experiences during their past menstrual cycle despite most of the respondents were able to meet their materials and home environment needs (n=27, 67.5%) and are less concerned when managing the disposal of their menstrual materials (n=25, 62.5%). Though, only 12.5% (n=5) of respondents have their transportation and school environment needs were met during their past menstrual cycle and 37.5% (n=15) of the respondents have concerns with the quality of their menstrual materials. The most common menstrual materials used by respondents at home and while away from home are disposable sanitary pads (n=35, 87.5% and n=36, 90.0% respectively). Many of the respondents prefer to dispose them inside the household rubbish bin which is inside the latrine when at home (n=36, 90.0 %) while the bin in the public latrine or toilet is used when disposing menstrual materials while away from home (n=32, 80.0%). Conclusion: Most of the female Rohingya refugees were able to practice safe and clean menstrual management. Though, some of their needs were not met, especially during transportation and away from home. It is important for non-government organizations like UNHCR to fight for their legal status in Malaysia so that they can feel safe and secure without it impacting their health negatively. International Journal of Human and Health Sciences Supplementary Issue: 2023 Page: S17